Impactos dos investimentos no setor energético brasileiro sobre as emissões de CO2: uma abordagem de equilíbrio geral computável - Viana, Jorge Henrique Norões (2011)
This study analyses the effects of an increase in investments to energy production, over the emissions of CO2 and the main macroeconomic variables. The data required for their preparation were obtained from the Ministry of Mines and Energy, the IBGE and the Intergovernmental Panel on Climate Change. To meet these goals, the energy inputs were divided into two groups: energy "clean" and "dirty"; based on their coefficients of CO2 emissions in 2006. Then, were simulated scenarios with: increases in investment equivalent to 1% of GDP in 2006, for each energy group, as well as scenarios involving an environmental tax of R$ 100.00 per ton of CO2; for a time horizon of ten years, using a sequential Computable General Equilibrium Model. The results of these simulations showed that there was a direct relationship between increased investments in energy and: the process of capital accumulation, the real GDP growth, the evolution of welfare, the evolution of CO2 emissions and changes in the intensity of CO2 pollution. Meanwhile, the results for simulations involving the environmental tax shown that it implied, in general, in: slowdown in capital accumulation, GDP growth below the steady state, a strong reduction of welfare and increasing reductions of emissions and intensity of pollution. Especially, the combination of an increase in investments for clean energy production, with the adoption of the environmental tax, was able to generate, simultaneously: accelerated accumulation of capital (2,70%) and real GDP growth (1,08%), increase of the welfare (R$ 33 billion) and reduction of the emissions (-1,21%) and intensity of pollution (-2,26%).